Perancangan dan Implementasi Jaringan VPN Dengan Metode L2TP/IPSec pada Kantor Cabang dan Kantor Pusat - Bambang Febrianto (CV. Multi Kreasi Media, 2022)
PT. BICOM MITRA SOLUSINDO is a business entity that was established in early 2008 which focuses on providing IT services to customers, one of the customers where to access data and applications branch office employees need to come to the location so it is very inefficient and takes a long time. Based on these problems, the researchers are interested in conducting a research entitled